Attack on Titan. 26 - Isayama, Hajime, 1986- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
As the dangerous rebel Eren Yeager mows down civilians and deals a massive blow to the Marleyan army, the Eldian soldiers, including Mikasa, Connie, and Sasha, spread chaos in the city and disrupt military communications.